DYSTOCIA DUE TO BREECH PRESENTATION OF AN OVERSIZED FETUS IN A BITCH - A CASE REPORT - MEHROTRA, S; DUTT, RAVI (The Indian Journal of Animal Reproduction, 2023)
A case of an obstructive fetal dystocia due to breech presentation of an oversized fetus followed by inertia of exhaustion (sencondary uterine inertia) and its successful clinical management is discussed.